2012
DOI: 10.1016/j.virol.2012.09.026
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of mycobacteriophage diversity and host preference

Abstract: The complete genome sequences of over 220 mycobacteriophages reveal them to be highly diverse, with numerous types sharing little or no nucleotide sequence identity with each other. We have determined the preferences of these phages for M. tuberculosis and for other strains of M. smegmatis, and find there is a correlation between genome type (cluster, subcluster, singleton) and host range. For many of the phages, expansion of host range occurs at relatively high frequencies, and we describe several examples in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
194
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(202 citation statements)
references
References 70 publications
4
194
0
1
Order By: Relevance
“…The third protein is Basilisk's tail fiber protein (gp51), which is one of only two proteins also encoded by JL and Shanette (38% identity). Since all three phages display the same host range (Table 1), these results are consistent with tail fibers being a highly recombinogenic host determinant (63,64). The tail fiber has homology to carbohydrate binding proteins (CenC from B. cereus is 43% identical over 103 amino acids), which suggests that carbohydrates are involved in host recognition.…”
Section: Figsupporting
confidence: 70%
“…The third protein is Basilisk's tail fiber protein (gp51), which is one of only two proteins also encoded by JL and Shanette (38% identity). Since all three phages display the same host range (Table 1), these results are consistent with tail fibers being a highly recombinogenic host determinant (63,64). The tail fiber has homology to carbohydrate binding proteins (CenC from B. cereus is 43% identical over 103 amino acids), which suggests that carbohydrates are involved in host recognition.…”
Section: Figsupporting
confidence: 70%
“…The cluster M phages thus represent an interesting new group displaying a variety of novel features. We have suggested previously that the broad span of mycobacteriophage diversity and their broad range of GC contents reflects an evolutionary history in which phages migrate rapidly across a landscape of closely related but diverse bacterial hosts at relatively high frequencies (20). The cluster M phages may thus have accessed M. smegmatis mc 2 155 as a host in their recent evolutionary past but took a distinct evolutionary path, accessing a spectrum of hosts that differs from that of mycobacteriophage clusters.…”
Section: Discussionmentioning
confidence: 99%
“…The origins of all this diversity are not clear, but it has been suggested that it reflects the ability of the viruses to relatively rapidly switch from one host to another. This ability then enables a speedy migration across the bacterial landscape, provided that a diverse set of relatively closely related bacterial cells is present in that environment (20). Viral genomes are architecturally mosaic, and gene acquisition by horizontal exchange provides a mechanism for rapid adaptation to new host environments (13,20,21).…”
Section: Mycobacteriophages-viruses Of Mycobacterial Hosts Such Asmentioning
confidence: 99%
“…These variations might be associated with the ability to expand their host range as observed for L5-like viruses (24). Also, keeping in mind that the number of protein encoding genes is constant for members of a particular virus species, the differential distribution of SSRs introduces variable potential in the genomes to evolve through copy number and sequence alterations.…”
Section: Prevalence Of Ssr and Cssrmentioning
confidence: 99%